Meningkatkan Kompetensi Guru TK Dalam Menyusun RPPH Melalui Supervisi Indent Penilik PAUD - Sri Ervawati (JURNAL GLOBAL EDUKASI, 2022)
Abstract: In the implementation of teaching and learning activities in several kindergartens in Binjai District, Langkat Regency, it was found that many educators/teachers had not been able to prepare RPPH. Then the inspector applies the Supervision Indent action to the educator. The results before the action obtained an average score of 40 which was obtained by kindergarten teachers in Binjai District in 2019 in compiling the RPPH and after being given the action in cycle 1, an average score of 70 was obtained, there was an increase of 30 points which showed an increase in educators in compiling the RPPH, but has not shown any improvement. the desired result of the researcher. Then it was continued to give action in Cycle II, the average score of educators was 90. There was an increase in the ability to prepare educators' RPPH by 20 points from cycle I, so this research is said to be complete because it has met the criteria for maximum completeness. Looking at the data obtained from the research results in this school action research activity, it can be concluded that the Indent Supervision carried out by the inspectors of 10 teachers who had difficulties in preparing the RPPH, succeeded in improving the pedagogic competence of educators in planning their daily learning well. Keywords: pedagogic competence; coaching; indent supervision  Abstrak: Dalam pelaksanaan kegiatan belajar mengajar beberapa TK di Kecamatan Binjai kabupaten Langkat ditemukan tenaga pendidik/guru banyak yang belum mampu menyusun RPPH. Lalu penilik menerapkan tindakan Supevisi Indent kepada pendidik. Hasil sebelum tindakan diperoleh rata-rata skor 40 yang didapat guru TK di Kecamatan Binjai Tahun 2019 dalam menyusun RPPH dan setelah diberi tindakan siklus 1 diperoleh rata-rata skor 70, terdapat peningkatan 30 poin yang menunjukkan peningkatan yang  pendidik dalam menyusun RPPH, namun belum menunjukkan hasil yang diinginkan peneliti. Maka dilanjutkan memberi tindakan di Siklus II, diperoleh hasil rata-rata pendidik skornya 90. Terjadi peningkatan kemampuan menyusun RPPH pendidik sebanyak 20 poin dari siklus I, maka penelitian ini dikatakan tuntas karena sudah memenuhi kriteria ketuntasan maksimal. Melihat data perolehan hasil penelitian dalam kegiatan penelitian tindakan sekolah ini, dapat disimpulkan bahwa Supevisi Indent yang dilakukan penilik terhadap 10 orang guru yang memiliki masalah kesulitan menyusun RPPH tersebut, berhasil meningkatkan kompetensi pedagogik pendidik dalam menyusun perencanaan pembelajaran harian mereka dengan baik. Kata Kunci: kompetensi pedagogic; pembinaan; supervisi indent